Optimal management of shoulder impingement syndrome - Escamilla RF; Hooks TR; Wilk KE (Dove Medical Press, 2014)
Rafael F Escamilla,1,2 Todd R Hooks,3 Kevin E Wilk4 1Department of Physical Therapy, California State University, Sacramento, CA, USA; 2Andrews Research and Education Institute, Gulf Breeze, FL, USA; 3Drayer Physical Therapy Institute, Columbus, MS, USA; 4Champion Sports Medicine, Birmingham, AL, USA Abstract: Shoulder impingement is a progressive orthopedic condition that occurs as a result of altered biomechanics and/or structural abnormalities. An effective nonoperative treatment for impingement syndrome is aimed at addressing the underlying causative factor or factors that are identified after a complete and thorough evaluation. The clinician devises an effective rehabilitation program to regain full glenohumeral range of motion, reestablish dynamic rotator cuff stability, and implement a progression of resistive exercises to fully restore strength and local muscular endurance in the rotator cuff and scapular stabilizers. The clinician can introduce stresses and forces via sport-specific drills and functional activities to allow a return to activity. Keywords: rotator cuff impingement, internal impingement, overhead athlete, shoulder, rehabilitation